Bile salt export pump is dysregulated with altered farnesoid X receptor isoform expression in patients with hepatocellular carcinoma12. Issue 4 (15th February 2013) - Chen, Yuan; Song, Xiulong; Valanejad, Leila; Vasilenko, Alexander; More, Vijay; Qiu, Xi; Chen, Weikang; Lai, Yurong; Slitt, Angela; Stoner, Matthew; Yan, Bingfang; Deng, Ruitang
Abstract As a canalicular bile acid effluxer, the bile salt export pump (BSEP) plays a vital role in maintaining bile acid homeostasis. BSEP deficiency leads to severe cholestasis and hepatocellular carcinoma (HCC) in young children. Regardless of the etiology, chronic inflammation is the common pathological process for HCC development. Clinical studies have shown that bile acid homeostasis is disrupted in HCC patients with elevated serum bile acid level as a proposed marker for HCC. However, the underlying mechanisms remain largely unknown. In this study, we found that BSEP expression was severely diminished in HCC tissues and markedly reduced in adjacent nontumor tissues. In contrast to mice, human BSEP was regulated by farnesoid X receptor (FXR) in an isoform‐dependent manner. FXR‐α2 exhibited a much more potent activity than FXR‐α1 in transactivating human BSEP in vitro and in vivo. The decreased BSEP expression in HCC was associated with altered relative expression of FXR‐α1 and FXR‐α2. FXR‐α1/FXR‐α2 ratios were significantly increased, with undetectable FXR‐α2 expression in one third of the HCC tumor samples. A similar correlation between BSEP and FXR isoform expression was confirmed in hepatoma Huh7 and HepG2 cells. Further studies showed that intrahepatic proinflammatory cytokines, such as interleukin‐6 (IL‐6) and tumor necrosis factor alpha (TNF‐α), were significantly elevated in HCC tissues. Treatment of Huh7 cells with IL‐6 and TNF‐α resulted in a marked increase in FXR‐α1/FXR‐α2 ratio, concurrent with a significant decrease in BSEP expression. Conclusion: BSEP expression is severely diminished in HCC patients associated with alteration of FXR isoform expression induced by inflammation. Restoration of BSEP expression through suppressing inflammation in the liver may reestablish bile acid homeostasis. (HEPATOLOGY 2013)